A New Seismic Response Control Technique for Buildings Using Block And Tackle - Saito, Taiki (2019)
The author proposed a new seismic response control system using a block and tackle (hereinafter, referred to as a dynamic pulley damper system) developed especially for the high-rise buildings. The proposed system has a configuration where a damper is installed on the track of the cable-stayed wire, amplifying the amount of movement of the wire by using a movable pulley that increases the damping effect to reduce the vibration of a building. we apply this system to connect the core structure (parking tower) and the surrounding frame (housing part) of a high-rise building. This system aims to reduce the earthquake response of the building by the force of the damper attached to the core structure. To verify the effectiveness of this response control system, two types of shaking table tests were conducted; one is the large-scale shaking table test using a magnetic damper, an-other one is the small-scale shaking table test using a steel damper. The mathematical model of the dynamic pulley damper system to implement the frame analysis was developed and the results of simulation analysis are compared with the experiments.